Devising an analytical method for estimating aircraft positioning accuracy by an infocommunication network of optoelectronic stations - Tevyashev, Andriy; Zemlyaniy, Oleg; Shostko, Igor; Kostaryev, Dmytro; Paramonov, Anton (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is the monitoring processes of airspace in the visible and infrared frequency ranges using an infocommunication network of optoelectronic tracking stations. The problem addressed is the assessment of accuracy in positioning aerial vehicles in airspace, considering random and systematic errors in video surveillance. The proposed method allows for the analytical evaluation of variance in the coordinates of aerial vehicles in airspace at any given moment, depending on the variance in errors from all components of the video surveillance process. The following results are reported: – mathematical models for both open and covert video surveillance by the infocommunication network of optoelectronic stations based on the trajectories of aerial vehicles, which enable the estimation of their coordinates for each moment of video surveillance. – analytical relationships between the variance of geolocation of aerial vehicles and the variance of errors in all components of the video surveillance process. A key feature of the method is its practical independence on the type and size of aerial vehicles. The method requires the availability of metrological characteristics of the optoelectronic station instruments and synchronized measurements of azimuth, elevation angle (for covert), and slant range (for open video surveillance). The numerical values of the root mean square deviations of the positioning errors of aerial vehicles under various video surveillance conditions range from 0.1 to 0.35 meters, confirming the effectiveness of using the infocommunication network of optoelectronic stations as an instrumental tool for high-precision trajectory measurements.